Determinan Manajemen Laba Pada Perusahaan Jasa (Sub Sektor Transportasi) Yang Terdaftar Di BEI Tahun 2018-2021 - Akira Henur, Rizda; Ramashar, Wira (Jurnal Ilmiah Raflesia Akuntansi, 2023)
This study aims to examine the effect of profitability, leverage, firm size, and earnings power on earnings management. The population in this study consisted of 46 transportation sector companies listed on the Indonesia Stock Exchange with an observation period of 2018-2021. The sampling method in this study used a purposive sampling technique, namely a method taken based on certain characteristics with certain techniques as well and the number of samples in the study were 88 samples. Testing was carried out using the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach with the help of WarpPLS version 7.0 software used in data analysis and hypothesis testing. The results of the study found that the leverage variable has a negative effect on earnings management, while the profitability, firm size, and earnings power variables have no effect on earnings management. Keywords — Profitability, Leverage, Firm Size, Earnings Power, Earnings Management.